2019
DOI: 10.21830/19006586.402
|View full text |Cite
|
Sign up to set email alerts
|

Revisión sistemática de la repercusión fisiológica de los cursos militares operacionales cortos para el soldado

Abstract: Con el fin de identificar la repercusión fisiológica que tienen los cursos de combate en el soldado, se realizó una revisión sistemática de estudios sobre entrenamiento militar, tanto analíticos como experimentales, publicados entre 2008 y 2018 en revistas indexadas. Como resultado de la búsqueda, se encontraron 483 artículos, de los cuales, conforme a los criterios de inclusión, solo quedo un total de 48. Se concluyó que los cambios fisiológicos del soldado en cursos cortos evidencian, a nivel mundial, la imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…The control of body mass, especially muscle mass, is fundamental for the military, since some studies (Chuang et al, 2017;Silva et al, 2020) demonstrated the relationship between body mass and physical fitness. Military personnel with high body mass may have lower-than-expected performances for the operational functions they perform (Gomez et al, 2019). Regarding body composition, similar results to our study were observed after eight weeks of intervention (Santtila et al, 2008) and after 12 weeks (El Hage & Reis Filho, 2013;Campos et al, 2017), which reported body mass and waist circumference reduction.…”
Section: Discussionsupporting
confidence: 87%
“…The control of body mass, especially muscle mass, is fundamental for the military, since some studies (Chuang et al, 2017;Silva et al, 2020) demonstrated the relationship between body mass and physical fitness. Military personnel with high body mass may have lower-than-expected performances for the operational functions they perform (Gomez et al, 2019). Regarding body composition, similar results to our study were observed after eight weeks of intervention (Santtila et al, 2008) and after 12 weeks (El Hage & Reis Filho, 2013;Campos et al, 2017), which reported body mass and waist circumference reduction.…”
Section: Discussionsupporting
confidence: 87%
“…Adicionalmente, el curso se desarrolla en tres áreas, las cuales comprenden la formación básica, la formación profesional específica y el área socio -humanística, siendo la primera la de mayor relevancia para la presente investigación, debido a que está enmarcada en la preparación física necesaria para mostrar un desempeño adecuado durante el desarrollo del curso, y en la cual también el alumno estimula habilidades y destrezas en unidades de combate terrestre (Aparicio Gomez et al, 2019). De acuerdo con lo anterior, durante la formación técnica y táctica del curso de combate se imparten instrucciones de combate cuerpo a cuerpo, supervivencia de combate en el agua, trote de hasta 14 kilómetros, marchas con cargas, ejercicios de tiro mediante polígonos diurnos y nocturnos, manejo de armamento, entre otras; por último, a nivel socio-humanístico se destacan el liderazgo, espíritu de cuerpo o del combatiente, ética y honor militar.…”
Section: Introductionunclassified
“…It is important to point out that exercise, in general, offers health benefits in non-military populations (4). However, under adverse operational and climatic situations, exercise can produce undesired impacts on those being trained; this has been described in reviews by several military entities concerning short training courses (5). It has also been documented that exercise can produce changes in the subjects' body composition (6) (7) and in other aspects of physical fitness, which are not the subject of this chapter.…”
Section: Introductionmentioning
confidence: 99%